The Impact of PTSD on Functioning in Patients Seeking Treatment for Chronic Pain and Validation of the Posttraumatic Diagnostic Scale - Åkerblom, Sophia (Int J Behav Med, 2017)
PURPOSE: The purpose of this study was to assess the psychometric properties of a Swedish version of the Posttraumatic Diagnostic Scale (PDS); to investigate the prevalence of traumatic experiences, trauma types, and posttraumatic stress disorder (PTSD) in a sample of patients seeking treatment for chronic pain; and to examine how indices of pain-related functioning vary with a history of traumatic exposure and PTSD diagnostic status. METHOD: Participants were 463 consecutive patients with chronic pain referred for assessment at the Pain Rehabilitation Unit at Skåne University Hospital. RESULTS: The translated version of the PDS demonstrated high levels of internal consistency and a factor structure similar to that reported in previous validation studies using samples identified because of trauma exposure (not chronic pain), both of which provide preliminary support for the validity of this translated version. Based on their responses to the PDS, most patients (71.8%) reported one or more traumatic events with 28.9% fulfilling criteria for a current PTSD diagnosis. The patients with PTSD also reported significantly higher levels of pain interference, kinesiophobia, anxiety, and depression and significantly lower levels of life control, compared to patients exposed to trauma and not fulfilling criteria for PTSD and patients with no history of traumatic exposure. CONCLUSION: Consistent with previous research, a significant proportion of patients seeking treatment for chronic pain reported a history of traumatic exposure and nearly one third of these met current criteria for PTSD according to a standardized self-report measure. The presence of PTSD was associated with multiple indictors of poorer functioning and greater treatment need and provides further evidence that routine screening of chronic pain patients for PTSD is warranted. Self-report measures like the PDS appear to be valid for use in chronic pain samples and offer a relative low-cost method for screening for PTSD.